Podział zysku a efektywność zaangażowania kapitałów własnych w spółkach akcyjnych przemysłu rolno-spożywczego - Franc-Dąbrowska, Justyna (Relationship Between Profit Distribution and the Effectiveness of Equity Capital in Join Stock, 2008)
The object of this study was distribution of profit, which still remains a major financial measure. Fifteen companies operating in food processing industry listed on the Warsaw Stock Exchange in 2001-2004 were analyzed here. It was a cause and effect analysis of a comparative-descriptive character. The research hypothesis was positively verified: the effectiveness of equity capital in companies which took the decision about profit distribution was equal or bigger than in companies where the decision was not taken.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 161-171